2017
DOI: 10.1155/2017/5641604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Propylene Carbonate from Epoxide and CO2 Catalyzed by Carbon Nanotubes Supported Fe1.5PMo12O40

Abstract: Carbon nanotubes (CNTs) were functionalized and were then used as supports of Fe 1.5 PMo 12 O 40 (FePMo) Keggin heteropolyanions catalysts. The characterization of the resulting catalysts was investigated by inductively coupled plasma spectrometry (ICP), Fourier transform infrared (FTIR) spectra, X-ray diffraction (XRD), ultraviolet-visible (UV-Vis) light spectroscopy, and transmission electron microscopy (TEM). FTIR and XRD results confirmed that FePMo was bounded on CNTs successfully and the Keggin structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Carbon nanotubes-supported Fe 1.5 PMo 12 O 40 (theoretical formulas) obtained 57.7% propylene oxide conversion and 99.0% propylene carbonate selectivity, both activity and selectivity were higher than Fe 1.5 PMo 12 O 40 , Co 1.5 PMo 12 O 40 , Cu 1.5 PMo 12 O 40 , and Zn 1.5 PMo 12 O 40 (theoretical formulas). The good activity can be attributed to the well dispersion of the Fe 1.5 PMo 12 O 40 on the CNTs [87].…”
Section: Non-reductive Co2 Conversion To Carbonyl-contained Organimentioning
confidence: 99%
“…Carbon nanotubes-supported Fe 1.5 PMo 12 O 40 (theoretical formulas) obtained 57.7% propylene oxide conversion and 99.0% propylene carbonate selectivity, both activity and selectivity were higher than Fe 1.5 PMo 12 O 40 , Co 1.5 PMo 12 O 40 , Cu 1.5 PMo 12 O 40 , and Zn 1.5 PMo 12 O 40 (theoretical formulas). The good activity can be attributed to the well dispersion of the Fe 1.5 PMo 12 O 40 on the CNTs [87].…”
Section: Non-reductive Co2 Conversion To Carbonyl-contained Organimentioning
confidence: 99%
“…To improve the recyclability of the catalyst, researchers have begun to develop heterogeneous catalysts, mainly including metal oxides, molecular sieves, supported catalysts, and carbon nanotube-ionic liquids-based catalysts. Bhanage et al studied the catalytic performance of metal-oxide-catalyzed ring-opening addition reaction. The results showed that the catalytic performance of MgO and La 2 O 3 was better than that of ZrO 2 , CaO, ZnO, and CeO 2 .…”
Section: Introductionmentioning
confidence: 99%